On the centers of cubic polynomial differential systems with four invariant straight lines - Llibre, Jaume (Topological Methods in Nonlinear Analysis, 2020)
Assume that a cubic polynomial differential system in the plane has four invariant straight lines in generic position, i.e., they are not parallel and no more than two straight lines intersect in a point. Then such a differential system only can have 0, 1 or 3 centers.